Media Sosial dan Penyimpangan Perilaku Keagamaan Remaja dalam Perspektif Islam - Irawan, Dedi; Abbas, Pirhat; Arifullah, Moh. (Journal of Comprehensive Islamic Studies, 2023)
This article discusses social media and deviant religious behavior among teenagers. The main problem raised is why there is deviation in teenagers' religious behavior? This article comes from qualitative-literature research to obtain the latest data regarding the relationship between social media and deviant religious behavior in adolescents. The findings of this research indicate that deviations in adolescent religious behavior stem from negative use of social media. The presence of social media is actually very beneficial for human life, because social media provides various information and needs. However, when teenagers are immersed in social media, it is not uncommon for them to abandon their religious values, resulting in various violations and deviations from actual norms. In fact, Islam prohibits behavior that deviates from religious rules. Artikel ini membahas tentang media sosial dan penyimpangan perilaku keagamaan remaja. Permasalahan utama yang diangkat adalah mengapa terjadi penyimpangan perilaku keagamaan remaja? Artike ini berasal dari penelitian kualitatif-literatur untuk mendapatkan data terkini tentang kaitan media ssial dengan  penyimpangan perilaku keagamaan remaja. Temuan penelitian ini menunjukkan bahwa penyimpangan perilaku keagamaan remaja bermula dari pengunaan media sosial yang negatif. Kehadiran media sosial sebenarnya bermaanfaat sekali bagi kehidupan manusia, karena media sosial menyediakan berbagai informasi dan kebutuhan. Namun demikian, ketika para remaja tenggelam dalam media sosial, tidak jarang mereka menanggalkan nilai-nilai religiusitasnya sehingga terjadi beragam pelanggaran dan penyimpangan dari norma yang sebenarnya. Padahal,  Islam melarang perilaku yang menyimpang dari aturan keagamaan.